Ursolic Acid Enhances Doxorubicin Cytotoxicity on MCF-7 Cells Mediated by G2/M Arrest - Arifin, Ibrahim; Hermawan, Adam; Ikawati, Muthi; Haryanti, Sari; Anindyajati, .; Meiyanto, Edy (Indonesian Research Gateway, 2012)
Ursolic acid has been widely known to possess biological activity against numerousÂ tumor cell lines. Previous studies revealed its cytotoxicity on several cancer cells Â in vitro byÂ either inducing apoptosis or cell cycle modulation. This Â study was conducted to investigateÂ ursolic Â acidâs Â cytotoxicity Â solely Â and Â in Â combination Â with Â a Â chemotherapeutic Â agent,Â doxorubicin, Â on Â MCF-7 Â breast Â cancer Â cells, Â followed Â by Â observation Â on Â its Â mechanism.Â Cytotoxicity of single and combinational treatment of ursolic acid and doxorubicin on MCF-7Â breast cancer cells were conducted by using MTT assay. Single treatment was then evaluatedÂ by Â determining Â IC50 Â value, Â while Â combinational Â treatment Â was Â evaluated Â by Â analyzing Â cellÂ viability Â and Â evaluating Â combination Â index Â (CI). Â To Â explore Â the Â mechanism Â underlyingÂ cytotoxic Â effect Â on Â respected Â cells, Â further Â analysis Â on Â cell Â cycle Â profile Â of Â single Â andÂ combinational treatment was conducted by flow cytometry. Twenty four hours treatment ofÂ ursolic Â acid Â inhibited Â MCF-7 cellsâ growth with Â IC50 Â value Â of Â 37 Â ÂµM, Â while Â combinationalÂ treatment Â showed Â that Â several Â concentration Â combinations Â of Â ursolic Â acid Â and Â doxorubicinÂ exhibited Â synergism Â of Â cytotoxic Â activity Â on Â MCF-7 Â cells, Â giving Â optimum Â CI Â value Â of Â 0.54.Â Flow cytometric analysis showed that combinational treatment induced G2/M arrest in MCF-7 Â cells. Â These Â results Â show Â that Â ursolic Â acid Â is Â promising Â to Â be Â developed Â as Â either Â singleÂ chemopreventive Â agent, Â or Â as doxorubicinâs co-chemotherapeutic Â agent Â in Â breast Â cancerÂ treatment. Â Observation Â on Â the Â selectivity Â as Â part Â of Â safety Â aspect Â together Â with Â in silico, Â inÂ vitro, and in vivo study on its molecular mechanism should be conducted.Keywords: ursolic acid, doxorubicin,co-chemotherapeutic agent, breast cancer, cell cycle